Weighted projections and Riesz frames - Antezana, Jorge Abel (2005)
Let H be a (separable) Hilbert space and ekk≥1 a fixed orthonormal basis of H. Motivated by many papers on scaled projections, angles of subspaces and oblique projections, we define and study the notion of compatibility between a subspace and the abelian algebra of diagonal operators in the given basis. This is used to refine previous work on scaled projections, and to obtain a new characterization of Riesz frames.